A quantitative analysis on the effect of housing prices in South Africa due to the expansion of the black middle class between the period of 2004-2015 - Lipschitz, Adam (The IIE, 2018)
Since the end of apartheid in 1994, wealth distribution has become a major topic in South Africa as the previously disadvantaged majority of the population are now able to move up in their social classes. As more and more of the previously disadvantaged population enter the middle class, a greater number of people are now able to afford housing in middle class markets and so in theory, demand for housing should increase due to new entries in the market. Studying the growth of the black middle class in South Africa has become a subject of major interest to many scholars, economists and investors globally as they see the potential impact that an expanding black middle class has on the South African economy. Literature identifies several key factors that looks at national housing prices, as well as grouping the black middle class. This research paper investigates who is considered to be in the black middle class, based on income and what effect they have on housing prices. The research paper incorporates quantitative analysis on the relationship between the black middle class and housing prices in South Africa, in order to identify the level of significances between the two variables. Based on 2 correlation coefficient tests, the outcomes are contradictive. The first test results using nominal figures showed a strong relationship between the independent and dependant variable, however when adjusting housing prices for real growth numbers, the second test results show an insignificant relationship between the two variables.
Keywords: black middle class expansion; housing prices; grouping of the black middle class; South Africa; housing market growth